Kualitas Pelayanan Kefarmasian di Puskesmas Tampa Padang - Sahrianti S, Nini; Fajriansyah, Arif; Nasrullah, Nasrullah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Pharmaceutical services are a form of pharmaceutical care that aims to maintain the quality of pharmaceutical preparations and support the success of therapy undergone by patients in treatment. The level of patient satisfaction is one way to measure the quality of pharmaceutical services. The purpose of this study was to determine the level of patient satisfaction with pharmaceutical services at the Tampapadang Health Center. This study was a descriptive study using a measuring instrument in the form of a questionnaire containing a list of questions containing 5 dimensions of quality, namely reliability, responsiveness, empathy, tangible, and assurance of service quality. The sample size in this study was 67 respondents determined using accidental sampling. The results of the study showed that the level of satisfaction per dimension was: reliability = the majority was satisfied (100%), responsiveness = the majority was satisfied (97%), empathy = the majority was satisfied (100%), tangible = the majority was satisfied (99%), assurance = the majority was satisfied (96%). Overall, the majority of respondents stated that they were satisfied (99%). Based on the results of the study, it was concluded that patients were satisfied with the pharmaceutical services at the Tampa Padang Health Center.Keywords: pharmaceutical services; health center; satisfaction; patient ABSTRAK Pelayanan kefarmasian adalah wujud dari asuhan kefarmasian yang bertujuan untuk menjaga mutu sediaan farmasi dan menunjang keberhasilan terapi yang dijalani oleh pasien dalam pengobatan. Tingkat kepuasan pasien merupakan salah satu cara ukur untuk mengetahui kualitas pelayanan kefarmasian. Tujuan penelitian ini adalah untuk mengetahui tingkat kepuasan pasien terhadap pelayanan kefarmasian di Puskesmas Tampapadang. Penelitian ini adalah penelitian deskriptif dengan menggunakan alat ukur berupa kuesioner yang berisi daftar pertanyaan yang memuat 5 dimensi kualitas yaitu reliability, responsiveness, emphaty, tangible, dan assurance kualitas pelayanan. Ukuran sampel dalam penelitian ini adalah 67 responden yang ditentukan dengan menggunakan accidental sampling. Hasil penelitian menunjukkan bahwa tingkat kepuasan per dimensi adalah: reliability = mayoritas adalah puas (100%), responsiveness = mayoritas adalah puas (97%), empathy = mayoritas adalah puas (100%), tangible = mayoritas adalah puas (99%), assurance = mayoritas adalah puas (96%). Secara keseluruhan mayoritas responden menyatakan puas (99%). Berdasarkan hasil penelitian disimpulkan bahwa para pasien merasa puas terhadap pelayanan kefarmasian di Puskesmas Tampa Padang.Keyword: pelayanan kefarmasian; puskesmas; kepuasan; pasien